Cezanne (OTUD7B) regulates HIF‐1α homeostasis in a proteasome‐independent manner. (29th October 2014) - Bremm, Anja; Moniz, Sonia; Mader, Julia; Rocha, Sonia; Komander, David
Abstract The transcription factor HIF‐1α is essential for cells to rapidly adapt to low oxygen levels (hypoxia). HIF‐1α is frequently deregulated in cancer and correlates with poor patient prognosis. Here, we demonstrate that the deubiquitinase Cezanne regulates HIF‐1α homeostasis. Loss of Cezanne decreases HIF‐1α target gene expression due to a reduction in HIF‐1α protein levels. Surprisingly, although the Cezanne‐regulated degradation of HIF‐1α depends on the tumour suppressor pVHL, hydroxylase and proteasome activity are dispensable. Our data suggest that Cezanne is essential for HIF‐1α protein stability and that loss of Cezanne stimulates HIF‐1α degradation via proteasome‐independent routes, possibly through chaperone‐mediated autophagy.